Amelia and phocomelia in Finland: Characteristics and prevalences in a nationwide population-based study - Pakkasjärvi Niklas; Syvänen Johanna; Wiro Markus; Koskimies-Virta Eeva (WILEY, 2022)
Background: Amelia and phocomelia represent severe limb reduction defects. Specific epidemiologic data on these defects are scarce. We conducted a descriptive analysis of prevalence data in Finland during 1993-2008 to clarify the epidemiology nationwide in a population-based register study. We hypothesized that increasing maternal age would affect the total prevalence of each disorder.
Materials and methods: We collected information on all fetuses and infants affected by amelia and phocomelia during 1993-2008 from the National Register of Congenital Malformations in Finland. The clinical, laboratory, autopsy, and imaging data were re-evaluated where available for all cases found.
Results: A total of 23 amelia and 7 phocomelia patients were identified. Thalidomide was not an etiological factor in any of the cases. The total prevalence of amelia was 2.43 per 100,000 births. The live birth prevalence was 0.63 per 100,000 live births. The total prevalence of phocomelia was 0.74 per 100,000 births, and the live birth prevalence was 0.53 per 100,000 live births. Infant mortality in amelia and phocomelia was 67% and 60%, respectively.
Conclusions: Infant mortality is high among amelia and phocomelia. Most cases had other major associated anomalies, but syndromic amelia cases were rare. Total prevalences were higher than previously reported and showed an increase in prevalence toward the end of the study period. The percentage of elective terminations of pregnancy for these disorders is high. While isolated cases are rare, they most likely present a better prognosis. Thus, correct diagnosis is essential in counseling for possible elective termination.